1997
DOI: 10.1136/jcp.50.8.699
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of microscope slides with Aspergillus glaucus group A: a laboratory problem in the diagnosis of suspected mycotic infections.

Abstract: The microscopic examination of lesions of patients with suspected mycotic infections using slides purchased from foreign countries often showed hyphae. The slides and their wrappings were cultured successfully on Sabouraud dextrose-agar medium. A heavy growth of suspected aspergillus colonies was obtained. These colonies were investigated further by culturing them on both Czapek's solution agar and Malt extract agar. After macroscopic and microscopic examination the fungus was identified as Aspergillus chevali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Biological contamination of scientific laboratory equipment, such as microscope, incubator, refrigerator, freezer, gas flame, centrifuge, rotator, balance and so on, may pose a potential health risk to personnel who work, service, repair and handle the equipment (Sewell 1995; Ghadjari et al. 1997; Neely and Orloff 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biological contamination of scientific laboratory equipment, such as microscope, incubator, refrigerator, freezer, gas flame, centrifuge, rotator, balance and so on, may pose a potential health risk to personnel who work, service, repair and handle the equipment (Sewell 1995; Ghadjari et al. 1997; Neely and Orloff 2001).…”
mentioning
confidence: 99%
“…Biological contamination of scientific laboratory equipment, such as microscope, incubator, refrigerator, freezer, gas flame, centrifuge, rotator, balance and so on, may pose a potential health risk to personnel who work, service, repair and handle the equipment (Sewell 1995;Ghadjari et al 1997;Neely and Orloff 2001). This laboratory equipment is commonly used by several students every week, and the specific results indicated that the equipment was contaminated with fungi, and students and staff were potentially exposed while working to these instruments, and therefore these fungi, which cause transmittable diseases.…”
mentioning
confidence: 99%